Predicting the Intention of Millennial Moslems to Visit Halal Tourism - Saifudin, Saifudin; Puspita, Rosana Eri (EQUILIBRIUM, 2020)
The purpose of this paper is to investigate the factors that influence the intention to choose halal tourism in Indonesia using the Theory of Reasoned Action (TRA) model. Data samples used in this study were 265 respondents and processed with Statistical Package for the Social Sciences to test the significance of the regression model. The independent variables are attitude, subjective norm, and halal certification and its impact on behavioral intention. The results show that attitude, subjective norm, and halal certification have a positive and significant effect on behavioral intention to visit halal tourism. Halal tourism practitioners can estimate the behavior of prospective millennial visitors through this paper. As for academics, this paper is used for further research by integrating halal certification in TRA as a predictor of behavioral intention in millennial Moslems. Empirically this research is useful to increase understanding of halal tourism and visitor behavior. Halal tourism is a relatively new phenomenon for practitioners and academics. This study is an initial study investigating the determinants of millennial Moslems' visits through the TRA model. Therefore, this paper will be useful as an academics contributions about millennial Moslems to visit halal tourism in Indonesia and the world.